Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Pada Distro Magnetic Kabupaten Wajo - Nurman Dai; Ardi; Agus Purwanto (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2025)
This study aims to determine the consumer marketing strategy at the Magnetic Distro in Wajo Regency. The background of this study is based on the importance of marketing strategy in increasing sales, especially amidst competition between other entrepreneurs. Marketing strategy variables are measured through five indicators: price, place, product promotion and quality. Meanwhile, sales increase is measured through product indicators, income, customers, users and new variants. This study uses a quantitative approach with data collection techniques through questionnaires distributed to 51 respondents selected from a population of 105 consumers. The data analysis technique used is simple linear regression. The constant value of 23.783 indicates that sales increase by 23.783 if the marketing strategy variable is not changed. The marketing strategy has a regression coefficient of 0.066. This value indicates that sales increase by 0.284 if the marketing strategy is increased by one unit. The T test from the coefficients table on the pricing variable obtained a Tcount value = 523 with a significance value of 0.000 <0.05. Based on the F test results shown in the ANOVA table, the calculated F value was 274 with a significance value of 603 > 0.05. With an R2 value of 0.006.